Myelin sheath survival following axonal degeneration in doubly myelinated nerve fibers - Kidd, GJ (J Neurosci, 1991)
Axonal contact plays a critical role in initiating myelin formation by Schwann cells. However, recent studies of “double myelination” have indicated that myelin maintenance continues in Schwann cells completely displaced from physical contact with the axon. This raises the possibility either that diffusible trophic factors are produced by the axon, or that the axon is not required for myelin maintenance by these displaced Schwann cells. To test these hypotheses, the axons involved in double myelination in the mouse superior cervical ganglion (SCG) were transected surgically by a transganglionic lesion. The inferior pole of the SCG was resected to limit axonal regeneration. This method produced a typical Wallerian pattern of degeneration in the superior pole, without compromising the blood supply or introducing nonspecific trauma. EM analysis at 1 and 5 d postoperatively showed that initially the axon degenerated, followed by breakdown of the inner myelin sheath. In those configurations where the outer Schwann cell was only partly displaced from the axon, the outer myelin sheath degenerated simultaneously. However, in completely displaced internodes the outer sheath survived degeneration of the axon and inner sheath. Outer internodes remained intact for at least 5 weeks after transection (the longest time point in this study), at which time they enclosed reorganized processes of the inner Schwann cells, their basal lamina, and numerous collagen fibrils. Axonal regeneration within surviving outer internodes was rare and was characterized by the development of typical Remak ensheathment by the inner Schwann cells. We conclude that in the mouse SCG, myelin maintenance does not depend on the continued presence of the axon. These data suggest further that myelin breakdown in Wallerian degeneration may be initiated by mechanisms other than absence of a viable axon.